Analisis Permintaan Obyek Wisata Pemandian Mata Air Way Bekhak Kabupaten Tanggamus Dengan Pendekatan Travel Cost Method - Megeas Deselpan; Toto Gunarto (Journal on Education, 2023)
This study aims to find out how much the level of demand for Way Bekhak spring bathing attractions and the factors that influence it are the number of requests for way bekhak spring bathing attractions which are located in Sukaraja village, Gunung Alip sub-district, Tanggamus district. The analytical method used in this study is the Ordinary Least Square (OLS) method. Meanwhile, to measure economic value, the travel cost method is used to calculate the value of consumer surplus per individual per year. The dependent variable used in this study is the number of requests for the Way Behak spring bathing attraction and the independent variables include travel costs, distance, income, length of visit and tastes. The results of this study indicate that travel costs and income have a positive and significant relationship to the number of requests for the Way Behak Springs bathing attraction, while the variables of distance, length of visit and taste have a positive relationship and there is a significant influence on the number of requests for bathing attractions. way behak springs.